2017
DOI: 10.1080/16549716.2017.1346164
|View full text |Cite
|
Sign up to set email alerts
|

Sexual transactions between long distance truck drivers and female sex workers in South Africa

Abstract: Background: Female sex workers (FSWs) and long distance truck drivers (LDTDs) are considered key populations at high risk for HIV transmission due to high prevalence. The intersection of these mobile populations presents unique challenges in the fight against HIV and the movement towards reducing new infections. Objective: The purpose of this study was to explore the nature of sex trade along a particular transport route. Sexual transactions and the vulnerabilities that exist between these two groups with rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
4
23
1
Order By: Relevance
“…This latter finding is different from most of the previous studies on knowledge of HIV status and sexual behaviour, which took place among members of the general population and found that knowledge of HIV‐negative status was not associated with HIV risk‐related sexual behaviours . It is particularly encouraging that FSWs in this setting who learn that they are HIV‐negative forgo the opportunity to make almost triple the amount of money for a sex act without a condom compared to a sex act with a condom – presumably to protect themselves from HIV acquisition. Moreover, FSWs in this study did not appear to be making up for this lost income by increasing their number of clients, suggesting that they are prepared to take potentially substantial losses in income for a reduced risk of HIV acquisition.…”
Section: Discussioncontrasting
confidence: 87%
“…This latter finding is different from most of the previous studies on knowledge of HIV status and sexual behaviour, which took place among members of the general population and found that knowledge of HIV‐negative status was not associated with HIV risk‐related sexual behaviours . It is particularly encouraging that FSWs in this setting who learn that they are HIV‐negative forgo the opportunity to make almost triple the amount of money for a sex act without a condom compared to a sex act with a condom – presumably to protect themselves from HIV acquisition. Moreover, FSWs in this study did not appear to be making up for this lost income by increasing their number of clients, suggesting that they are prepared to take potentially substantial losses in income for a reduced risk of HIV acquisition.…”
Section: Discussioncontrasting
confidence: 87%
“…New HIV infections in Tanzania have been decreasing [4] however some populations are still at higher risk than the general population [5]. These key and vulnerable populations include; commercial sex workers, intra venous (IV) drug abusers and mobile population like, fishermen, prisoners and truck drivers [6–9]. In India, fishermen were reported to have uppermost HIV infection vulnerability however similar observation in Kenya and Uganda has been reported [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous findings from the United States [34] and South Africa [35] indicate that HIV transmission was identified along main trucking routes, association between HIV transmission and human migration has to date not been described for Germany. In fact, Cologne is one of the key hubs for national and international transportation routes, connecting northsouth and east-west, but it remains speculative if trucking routes may be driving interregional HIV transmissions in Germany.…”
Section: Discussionmentioning
confidence: 84%